Peran Barisan Muda Penegak Amanat Nasional (BM PAN) Lampung dalam Pengembangan Kepemimpinan Pemuda - Nadiyah Salamah; Dwi Khusnatunnisa; Rima Fadhilatunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
As a wing organization of the National Mandate Party, Barisan Muda Penegak Amanat Nasional (BM PAN) is strategically responsible for fostering youth leadership at the regional level, including in Lampung Province. The purpose of this study is to investigate the role of BM PAN Lampung in shaping the character of youth leadership through various training, advocacy, and cadre programs. The method used is a qualitative approach that uses participatory observation, documentation studies, and in-depth interviews to collect data. The study shows that BM PAN Lampung has the ability to facilitate constructive political participation for youth and become a place to build leadership skills oriented towards national values. This organization has shown that its cadre program has succeeded in increasing political awareness, public communication skills, and managerial skills among its members. In addition, as shown by Santoso (2014) and Mulyadi (2018) about the importance of youth participation in political regeneration, this study found that youth organizations such as BM PAN play an important role in enhancing participatory democracy at the local level.